Problem Based Learning Model Combination of Peer Tutor Improves Student Learning Outcomes - Liliyana Ayu Widyaningrum; Aniek Hindrayani; Muhammad Sabandi (Jurnal Pendidikan Indonesia, 2024)
The current learning problem is that learning activities could be more optimal. Lack of reading habits and students' attention to the subject matter being taught causes low student learning outcomes. Based on this, this research aims to analyze the influence of problem-based learning models and peer tutor learning methods on high school students' learning outcomes in Economics subjects. The type of research used in this research is quasi-experimental research. The population of 6 classes was selected randomly using cluster random sampling, totalling 216 students. The methods used to collect data are observation, questionnaires, documentation and tests. The instruments used to collect data were questionnaire sheets and test questions. The techniques used to analyze data are descriptive statistical analysis and inferential statistical analysis. The research results show that using the problem-based learning model combined with peer tutoring significantly affects student learning outcomes in economics subjects. The PBL learning method significantly affects learning outcomes, whereas the peer-tutor combination method can provide better learning outcomes than conventional methods. The problem-based learning model combined with peer tutors could significantly improve student learning outcomes.